An interesting case of aluminum phosphide poisoning - Gholamreza Faridaalaee; Sajjad Ahmadi; Seyed Hesam Rahmani; Amin Mahboubi (Journal of Emergency Practice and Trauma, 2016)
Ingestion and inhalation of phosphine are 2 forms of toxicity and their clinical manifestation is extremely wide. A 22-year-old girl was admitted with complaints of nausea, vomiting and epigastric pain after eating lunch. She had a history of celiac disease. On arrival, she was alert and hemodynamically stable. There was not any abdominal tenderness or guarding. Food poisoning treatment initiated but after 1 hour her condition deteriorated with hypotension, tachycardia, and epigastric pain. Venous blood gas (VBG) showed severe metabolic acidosis. She denied any drug ingestion again. New Electrocardiogram (ECG) showed extensive inferolateral ST elevation myocardial infarction (STEMI). Bicarbonate plus dopamine was initiated. After 8 hours of admission, rhythm became ventricular fibrillation (VF) and cardiopulmonary resuscitation (CPR) began. Peritoneal dialysis was performed. Next morning frequent VF occurred again but CPR was unsuccessful. Family found aluminum phosphide (AIP) tablets in her purse. Early diagnosis and supportive treatment may be effective but the most important factor is the dose of ingestion.